2008
DOI: 10.1002/eat.20510
|View full text |Cite
|
Sign up to set email alerts
|

A high‐fat diet prevents and reverses the development of activity‐based anorexia in rats

Abstract: Objective Activity-based anorexia is an animal model of anorexia nervosa in which limited access to standard lab chow combined with voluntary wheel running leads to hypophagia and severe weight loss. This study tested whether activity-based anorexia could be prevented or reversed with palatable foods. Method Male rats were divided into sedentary or ad libitum-running groups and maintained on 1 h daily access to standard chow plus one of the following: sugar, saccharin, vegetable fat (shortening), or sweet hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…A recent study using the ABA model has demonstrated the efficacy of a HFD in rescuing rodents from anorexia (Brown et al, 2008). However, feeding a HFD to human AN patients runs contrary to the characteristics of the disorder and attempts to do this have been shown to heighten anxiety associated with eating a high-caloric diet (Boutelle, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study using the ABA model has demonstrated the efficacy of a HFD in rescuing rodents from anorexia (Brown et al, 2008). However, feeding a HFD to human AN patients runs contrary to the characteristics of the disorder and attempts to do this have been shown to heighten anxiety associated with eating a high-caloric diet (Boutelle, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, the first line of treatment for underweight patients with AN, is feeding and weight restoration, combined with psychotherapy. In ABA rats, certain palatable diets have been found to affect the development of, and recovery from, ABA (Brown et al ., ). Evidence for the efficacy of drug treatments for AN is limited, and currently there are no FDA or EMA approved drugs for the treatment of AN.…”
Section: Treatment Of An With Monoaminergic Agentsmentioning
confidence: 97%
“…Because dopamine is integral to mesolimbic reward processing, it follows logically that central reward dysfunction in AN and ABA is associated with the DA disturbances described above, specifically within the mesolimbic reward circuit. Indeed, rodent studies indicate that the ABA phenotype can be ameliorated by increasing the hedonic or rewarding value of food, by substituting laboratory chow with a high‐fat diet alone or combined with delta‐9‐thetrahydrocannabinol (THC) administration, both of which have effects mediated by DA signalling …”
Section: Dopamine and Reward Disruptions In Abamentioning
confidence: 99%